Legal Implications of The Regulation of Material Legal Norms in A Supreme Court Regulation (PERMA) - Wahyu Iswantoro; Tunggul Anshari Setia Negara; Aan Eko Widiarto (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
Apart from being the authority of the DPR and the President, the 1945 Constitution of the Republic of Indonesia also gives authority to judicial institutions such as the Supreme Court to make or form regulations. Whereas following Article 79 Paragraph (1) of the Supreme Court Law, the authority to regulate the Supreme Court is limited to supplementing procedural law, however, in its development, several PERMAs such as PERMA 2/2012 regulate the content of material legal norms and are externally binding, which should be regulated at the level law and becomes the authority of lawmakers (legislative act). The main issue that is important to research is what are the legal implications of regulating material legal norms in a PERMA. Under the problems raised, this research is doctrinal research also known as normative research. The approaches used are a statutory approach and a conceptual approach. Based on the results of this research, there are 2 (two) legal implications of regulating material legal norms in a PERMA, namely: Overlapping Material Content of Legal Norms and the Unclear Position of PERMA in the Hierarchy of Legislative Regulations. As a result of these three legal implications, law enforcement officials as a legal structure will be unsure whether to follow PERMA as a statutory regulation that is aligned with the law or whether to ignore it.